Differentiating event‐related potential components sensitive to emotion in middle childhood: Evidence from temporal–spatial PCA. Issue 5 (12th June 2012) - Kujawa, Autumn; Weinberg, Anna; Hajcak, Greg; Klein, Daniel N.
Abstract Event‐related potentials (ERPs) may be particularly useful for examining emotional processing across development. Though a number of ERP components are sensitive to emotional content in adults, previous studies have yet to systematically examine the components sensitive to emotion in children. The current study used temporal–spatial principal components analysis (PCA) to identify ERP components in response to complex emotional images in 9‐year‐old children. Three components were modulated by emotional content and were similar to those previously observed in adults, including: the early posterior negativity, the P300, and a sustained relative positivity similar to the late positive potential (LPP). Compared to those previously observed in adults, the components sensitive to emotion in children were maximal over more occipital regions and the LPP component appeared to be less protracted in time, perhaps indicative of less elaborative processing of emotional stimuli. © 2012 Wiley Periodicals, Inc. Dev Psychobiol 55: 539–550, 2013